MENAKSIR VALUE AT RISK (VAR) PORTOFOLIO PADA INDEKS SAHAM DENGAN METODE PENDUGA VOLATILITAS GARCH - WAHARIKA, INTAN AWYA; DHARMAWAN, KOMANG; ASIH, NI MADE (E-Jurnal Matematika; Vol 2 No 1 (2013): E-Jurnal Matematika, 2013)
Value at Risk (VaR) is a concept which was used to measure a risk on risk management. VaR explained the worst amount of financial loss in a financial product with the horizon and certain degree of believe. In the calculation of VaR, it was needed a prediction in volality, volality from a series of time which can be homokedasticity (constant) or heterokedasticity (ever changed). Changed volality can be found on the stock and stock index. One of the method which was done in modeling of changed volality was GARCH. In this research, GARCH was used to estimate VaR’s Value from IHSG and LQ45 to be sold in Jakarta Stock Exchange on 4 January to 23 August 2012 (650 observations) VaR can be calculated with a periode of horizon, 1 day, 10 days, and 22 days with the degree of believe 95%
Keywords: Value at Risk; Volatility; GARCH